Pengaruh level substitusi minyak buah merah kasar dalam campuran patty daging rusa terhadap tingkat preferensi konsumen - Inggabouw, Tirza; Monim, Hanike; Baaka, Alnita; Pakage, Stepanus (Cassowary, 2026)
ABSTRACT: This study aimed to determine the effect of different levels of crude red fruit oil (CRFO) addition on the organoleptic characteristics and consumer preference of processed venison (Cervus timorensis) patties. The research was conducted experimentally using a Completely Randomized Design (CRD) with five treatments: P0 (without CRFO), P1 (15 ml), P2 (20 ml), P3 (25 ml), and P4 (30 ml), each with three replications. Organoleptic evaluation was carried out by 30 panelists assessing color, aroma, taste, tenderness, and overall acceptability using a five-point hedonic scale. The results showed that the addition of CRFO had a significant effect (P < 0.05) on color, but no significant effect (P > 0.05) on aroma, taste, tenderness, and overall acceptability. The highest mean preference scores for color were observed in treatments P1 (15 ml) and P2 (20 ml), while for other attributes, panelists tended to give favorable ratings (“like”) within the concentration range of 20–25 ml. Thus, the addition of CRFO up to 25 ml per 350 g of venison produced patties with desirable color and flavor characteristics preferred by consumers, indicating its potential for development as a functional food product based on local Papuan resources.